Bottom-up synthesis of graphene films hosting atom-thick molecular-sieving apertures - Villalobos, Luis Francisco; Van Goethem, Cédric; Hsu, Kuang-Jung; Li, Shaoxian; Moradi, Mina; Zhao, Kangning; Dakhchoune, Mostapha; Huang, Shiqi; Shen, Yueqing; Oveisi, Emad; Boureau, Victor; Agrawal, Kumar Varoon (Proceedings of the National Academy of Sciences - PNAS, 2021)
Incorporation of a high density of molecular-sieving nanopores in the graphene lattice by the bottom-up synthesis is highly attractive for high-performance membranes. Herein, we achieve this by a controlled synthesis of nanocrystalline graphene where incomplete growth of a few nanometer-sized, misoriented grains generates molecular-sized pores in the lattice. The density of pores is comparable to that obtained by the state-of-the-art postsynthetic etching (1012 cm-2) and is up to two orders of magnitude higher than that of molecular-sieving intrinsic vacancy defects in single-layer graphene (SLG) prepared by chemical vapor deposition. The porous nanocrystalline graphene (PNG) films are synthesized by precipitation of C dissolved in the Ni matrix where the C concentration is regulated by controlled pyrolysis of precursors (polymers and/or sugar). The PNG film is made of few-layered graphene except near the grain edge where the grains taper down to a single layer and eventually terminate into vacancy defects at a node where three or more grains meet. This unique nanostructure is highly attractive for the membranes because the layered domains improve the mechanical robustness of the film while the atom-thick molecular-sized apertures allow the realization of large gas transport. The combination of gas permeance and gas pair selectivity is comparable to that from the nanoporous SLG membranes prepared by state-of-the-art postsynthetic lattice etching. Overall, the method reported here improves the scale-up potential of graphene membranes by cutting down the processing steps.Incorporation of a high density of molecular-sieving nanopores in the graphene lattice by the bottom-up synthesis is highly attractive for high-performance membranes. Herein, we achieve this by a controlled synthesis of nanocrystalline graphene where incomplete growth of a few nanometer-sized, misoriented grains generates molecular-sized pores in the lattice. The density of pores is comparable to that obtained by the state-of-the-art postsynthetic etching (1012 cm-2) and is up to two orders of magnitude higher than that of molecular-sieving intrinsic vacancy defects in single-layer graphene (SLG) prepared by chemical vapor deposition. The porous nanocrystalline graphene (PNG) films are synthesized by precipitation of C dissolved in the Ni matrix where the C concentration is regulated by controlled pyrolysis of precursors (polymers and/or sugar). The PNG film is made of few-layered graphene except near the grain edge where the grains taper down to a single layer and eventually terminate into vacancy defects at a node where three or more grains meet. This unique nanostructure is highly attractive for the membranes because the layered domains improve the mechanical robustness of the film while the atom-thick molecular-sized apertures allow the realization of large gas transport. The combination of gas permeance and gas pair selectivity is comparable to that from the nanoporous SLG membranes prepared by state-of-the-art postsynthetic lattice etching. Overall, the method reported here improves the scale-up potential of graphene membranes by cutting down the processing steps.